Metodologías y Didácticas del Paso Básico, Desplazamientos y Valseo Implementadas en la Práctica Pedagógica para la Enseñanza del Joropo Escuela de Formación Artística del Municipio de Mosquera Cundinamarca (2022)
This degree work constitutes the culmination of the teacher's training process artist of the Artistic Education Degree with Emphasis in Dance and Theater. its developments, contributions, scope, questions and projections, contribute to the growth of the Research Group Didactics of the Performing Arts and is part of the Teacher's Thought Line for the Arts. as part of this, Methodologies and Didactics of the Basic Step, Displacements and Valseo of the Joropo Implemented in the Pedagogical Practice for the Teaching of Joropo, School of Artistic Training of the Municipality of Mosquera Cundinamarca. In this way, the present investigation contributes significantly by demonstrating the interest in addressing the different methodologies and didactics for the implementation of the basic concepts of the joropo, evidencing its application in the pedagogical practice carried out in the School of Artistic Training of Mosquera, taking into account two referents of the territory llanero, the teacher Astrid Carolina Arenas-Vanegas and the teacher Álvaro Enrique Rico-Sánchez. For this reason, a method is used that allows the collection of information with the purpose of analyze, triangulate and obtain valuable results, thus realizing a symbiosis in Regarding the pedagogical and artistic aspects of the teachers, studied and applied by the Master artist in training. These obtained investigations are of great value since they validate the recognition and exposure of those methodologies and didactics implemented from the step basic, displacements and waltzing of the joropo. In this sense, with the collection obtained, created an audiovisual material that reports and collects the most relevant information, called "capsule" which is the summary of what has been implemented in the process of pedagogical practice of the Master artist in training.